On massive photons inside a superconductor as follows from London and Ginzburg–Landau theory - Ouboter, R. de Bruyn; Omelyanchouk, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
A phenomenological derivation in the frame of London`s and Ginzburg–Landau theories is given that photons behave inside a superconductor as if they have mass.